Uji potensi bioherbisida kiambang (Salvinia molesta) dalam menekan pertumbuhan gulma babadotan (Ageratum conyzoides) - Yus Dwi Yanti; Limartaida Siahaan; Mahmudin; Dora Palupi; Helda Susianti; Ferdiansyah (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
Kiambang is an aquatic weed commonly found in Indonesian waters. Kiambang extract contains secondary metabolite compounds that have the potential to inhibit the growth of billygoat weed (Ageratum conyzoides), which is commonly found in agricultural and plantation areas. This study was conducted to determine the potential of kiambang extract as a bioherbicide against billygoat weed. The study employed a Completely Randomized Design (CRD) consisting of five concentrations of kiambang extract, namely 0%, 20%, 40%, 60%, and 80%, with four replications. The observed parameters included weed mortality percentage, weed height, and bioherbicide efficacy. A significant effect on bioherbicide efficacy was first observed at a concentration of 40%, resulting in an efficacy value of 7.18%, while the highest efficacy was achieved at 60% concentration (42.46%). Meanwhile, significant effects on weed mortality percentage and weed height were observed starting at a concentration of 60%. Kiambang extract can be utilized as a contact bioherbicide for controlling billygoat weed, commonly found in agricultural and plantation areas.